Sterilization, monetary policy, and global financial integration - Joshua Aizenman; Reuven Glick (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
This paper investigates the changing pattern and efficacy of sterilization within emerging market countries as they liberalize markets and integrate with the world economy. We estimate the marginal propensity to sterilize foreign asset accumulation associated with net balance of payments inflows, across countries and over time. We find that the extent of sterilization of foreign reserve inflows has risen in recent years to varying degrees in Asia as well as in Latin America, consistent with greater concerns about the potential inflationary impact of reserve inflows. We also find that sterilization depends on the composition of balance of payments inflows.
Keywords: F15; F21; F31; 330; foreign reserves; international reserves; sterilization; global financial integration; Kapitalmarktregulierung; Geldpolitik; Wechselkurspolitik; Währungsreserven; Kapitalimport; Finanzmarktkrise; Aufstrebende Märkte